Discourse strategies used by hosts of Malaysian radio talk shows - Lee, Soo Yee Esther (Journal of Modern Languages, 2017)
This study investigates the discourse strategies used by hosts of local expert-advice phone-in talk shows in English. The objective of the study is to examine the discourse strategies used by hosts of radio phone-in talk shows in Malaysia, with regard to conversational turn-taking and topic management. The study also seeks to investigate the ways in which these strategies are affected by the institutional nature of phone-in radio talk shows, and the presence of an overhearing audience.